A Coroa e a esfera: cosmografia e poder nas obras de Pedro Nunes (1537-1573) - Barbosa Neto, Geraldo (2017)
This investigation is about the articulations of the cosmographic knowledge with the problem of the physical and conceptual distance between the monarchical state of the Portuguese and the places of the world that composed its maritime empire. It is bordered in Portugal from the 16th century. Its scope is to reveal an interpenetration between the cosmographic production and the problem of the physical and conceptual distance between the Lisbon Palace and the coasts, islands and firm lands under its lordship, using as its historical source the works of Pedro Nunes (Alcácer do Sal, 1502 - Coimbra, 1578), cosmographer of the King of Portugal D. João III (1502-1557). It leads us to a historical framework in which power and science mingle. It introduces us to a historical conjuncture, in which a history of politics and a history of the sciences intertwine and complement each other